PREACHING BILL HIKMAH IN A PLURAL CONTEXT: STUDY OF JURGEN HABERMAS'S COMMUNICATION PARADIGM - Muhamad Abdul Manan; Mahmudi, Mahmudi; Muis, Abdul; Al Ghifari , Abudzar (Progresif : Media Publikasi Ilmiah, 2024)
This article explores the concept "Preaching Bill Hikmah" (wisdom-based preaching) in the context of pluralism through Jürgen Habermas' communication paradigm. This article discusses the importance of ethical communication in da'wah, emphasizing the need for integrity on both the part of the preachers and their audiences. This article explains how Habermas's notion of communicative action can provide a framework for building interreligious dialogue, promoting tolerance and understanding. Reinforcing the idea of ​​pluralism, this study highlights the importance of creating space for interfaith dialogue and emphasizes the need to unite various interpretations of Islam to counter radicalism and increase community cohesion. This research uses a descriptive qualitative research method with a literature study approach. The results of this research show that Jürgen Habermas's communication paradigm, especially the concept communicative action, can be adapted in the context of da'wah to encourage inclusive, tolerant and ethical dialogue. This allows da'wah to become a unifying tool in a pluralistic society, where wisdom-based communication can reduce potential conflict, fight the spread of radicalism, and strengthen social harmony.